Interaction between young fecal transplantation and perfluorobutanesulfonate endocrine disrupting toxicity in aged recipients: An estrobolome perspective - Baili Sun; Chenyan Hu; Jiali Li; Zixie Yang; Lianguo Chen (Environment International)
Transplanting young feces into the aged was found to effectively counteract the endocrine disrupting effects of perfluorobutanesulfonate (PFBS) pollutant, showing promise in the maintenance of healthy aging. However, the interactive mechanisms between young fecal transplantation and PFBS endocrine disruption during aging remain unclear. In this follow-up study, aged zebrafish were administered young donor feces and then exposed to environmentally relevant concentrations of PFBS (0 and 100 μg/L). Alterations in the holistic estrobolome along gut-liver axis were investigated. The results showed that PFBS singular exposure significantly increased blood estradiol concentration in the aged, inducing an estrogenic activity. Concentrations of other estrogen forms, including estrone and estriol, were also disrupted by PFBS. Interestingly, young fecal transplant effectively mitigated the estrogenic toxicity of PFBS and largely restored estrogen equilibrium. After PFBS exposure, the transcriptions of estrogen metabolic genes were consistently upregulated in aged livers, causing the accumulation of 2-methoxyestradiol-3-methylether metabolite. In contrast, aged livers coexposed to young fecal transplant and PFBS enhanced the glucuronidation process, successfully facilitating the elimination and detoxification of estrogen metabolites. In aged gut, PFBS exposure inhibited β-glucuronidase enzyme activity, implying the suppression of estrogen deconjugation and recycle. However, in the combined group, β-glucuronidase activity was significantly stimulated, thus reestablishing estrobolome dynamics. Overall, current findings provide mechanistic insights into the antagonistic interaction between young fecal transplant and PFBS on reproductive endocrinology. Gut microbiota manipulation appears appealing to maintain healthy aging progression albeit the interruption of environmental xenobiotics.